2018
DOI: 10.1002/cvj.12088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self‐Transcendent and Self‐Enhancement Values on Compassion, Humility, and Positivity in Marital Relationships

Abstract: The authors investigated the degree to which self‐enhancement and self‐transcendent values relate to spousal reports of compassion, humility, and positivity in marital relationships. The data were drawn from a self‐report telephone survey of 1,513 heterosexual married individuals living in the United States in 2013. Results indicate that self‐transcendent values positively relate to compassion, humility, and positivity, whereas self‐fulfillment values relate only to positivity. These results did not differ by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Twenty-one tests reported no significant differences in compassion by gender. In the one study that reported greater compassion among males, spouses were asked to rate the level of compassion of their spouse; in this case, wives were more likely to rate their husbands as compassionate than vice-versa ( McDonald et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one tests reported no significant differences in compassion by gender. In the one study that reported greater compassion among males, spouses were asked to rate the level of compassion of their spouse; in this case, wives were more likely to rate their husbands as compassionate than vice-versa ( McDonald et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies that examined positive attitudes towards compassion ( Kirby et al, 2021 ), egalitarian values ( Owuamalam and Matos, 2019 ), or self-transcendent values ( McDonald et al, 2018 ) found positive associations with compassion. As defined by McDonald et al (2018) , self-transcendent values are closely related to eudaimonia (happiness arising from fulfilling one’s virtuous potential) and well-being.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And it is linked to greater professional success, better problem solving, good health (Zepeda-Goncen & Sánchez-Aragón, 2021) and a longer life (Peterson, 2000). Aragón the couple, among which CL and optimism stand out for generating intimacy, inspiring warm feelings, openness and the desire to be reciprocal, facilitating forgiveness, satisfaction and commitment (McDonald, Olson, Goddard, & Marshall, 2018). According to these authors, optimism enriches creativity, the ability to solve problems in a more cooperative and constructive way (Assad, Donnellan, & Conger, 2007;Neff & Geers, 2013) and it has positive effects on energy, which predisposes individuals to seek that their partners are also happy and welfare not only individually but also within the relationship (e.g., Williamson, Karney, & Bradbury, 2013), which is particularly evident in women (Goddard, Olson, Galovan, Schramm, & Marshall, 2016).…”
mentioning
confidence: 99%